(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The study’s goal is to learn about SME perceptions of using e-commerce platforms and to analyse the amount of adoption that SMEs are absorbing. The data for the research is primary in nature and was gathered through questionnaire. The SPSS programme and statistical techniques were used in the study. According to a study SMEs, most of the SMEs are still in the early phases of e-commerce adoption. According to the findings of the study, SMEs place a higher value on improved customer interactions and 24-hour accessibility. Managing client relationships online has now become a vital aspect of establishing a company. Payment satisfaction has also grown dramatically as a result of the 24/7 system availability and enhanced client experience. Most SMEs are also satisfied with the available opportunities, which include many different variables along with five components, and many SMEs have graded for higher than 0.7 of the factors in which they are satisfied. E-commerce has the potential to provide a competitive edge for SMEs. E-commerce is a low-cost method of reaching out to consumers all over the world and competing with huge corporations.